2022
DOI: 10.1177/10778012221085998
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and Discrimination Experienced by Older Women in the Era of COVID-19: A Two-Wave Representative Community Survey in Hong Kong

Abstract: Although there is a growing volume of research on violence against women, violence against older women has received little attention to date. Little is known about the experience of elder abuse, discrimination, loneliness, and health among older women, in particular in the era of COVID-19 when our lives have been changed drastically. Using two waves of survey data ( N = 1,498), this study compared the estimates of elder abuse and age discrimination before and during the COVID-19 pandemic, examined their associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…The finding of increased physical and emotional abuse directly contrasts a study reporting a decrease in physical and psychological abuse during the pandemic compared to a pre-pandemic period in a representative community sample of older women in Hong Kong [12]. Our findings also diverge slightly from of Chang et al [10] who found increases in rates of physical abuse and financial abuse reported during the pandemic period, but not in verbal abuse (a type of emotional abuse).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding of increased physical and emotional abuse directly contrasts a study reporting a decrease in physical and psychological abuse during the pandemic compared to a pre-pandemic period in a representative community sample of older women in Hong Kong [12]. Our findings also diverge slightly from of Chang et al [10] who found increases in rates of physical abuse and financial abuse reported during the pandemic period, but not in verbal abuse (a type of emotional abuse).…”
Section: Discussioncontrasting
confidence: 99%
“…Differences between studies may also reflect the complexity of measuring elder abuse during the COVID-19 pandemic. For example, Yan et al [12] discuss that the reduction in elder abuse found in their study may reflect a true reduction in elder abuse as a result of changing living situations, or may reflect a change in the willingness to report elder abuse during the pandemic period when more victims are trapped at home with perpetrators of violence. Thus, different data sources (i.e., survey, resource line) may yield vastly different results.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All data were collected using a computer-assisted telephone interview (CATI) system. More detailed information about the recruitment procedures were described in a previous paper [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perceived risk was measured by the question asking the participants to rate the chance that the participant himself/herself be infected by COVID-19 along a ve-point scale ranging from 'no chance at all' (1) to 'very great chance' (5).…”
Section: Measures Depression Is the Dependent Variable Measured By Th...mentioning
confidence: 99%